How the people of Aceh perceive western and Islamic democracy (A study based on political marketing approach) - Hafasnuddin Hafasnuddin (Proceedings of AICS - Social Sciences, 2017)
The objective of this study was to analyze the comparison of Acehnese perceptions towards the application of western democracy and Islamic democratic system or democracy containing Islamic values in Aceh based on political marketing approach. The study was done by the end of 2016 in Aceh Province (Indonesia) by using a qualitative approach. Samples were chosen based on purposive sampling as many as 22 people who understood democracy either theoretically or practically, then interviewed in depth at a separate place. The data obtained were analyzed qualitatively by using the approach of political marketing theory. The study found some interesting findings, among others, first: the western democratic system was initially accepted by the people of Aceh but they were not satisfied with the performance of elected leaders through the western democratic system. Second, Islam has its own system of democracy applied through Ahlul Halli wal 'Aqdi. Third, the people of Aceh perceived positively to the democracy of Islam or democracy containing Islamic values because through such a democratic system was expected to be elected leader who truly represented the people of Aceh, a trustful leader, a leader who thought for all the people of Aceh instead of thinking only his party, a leader who executed sharia law in all aspects of Islam (kaffah), a leader who was really serious about eradicating corruption, and restoring Aceh to its prime-time glory. This type of leader will not be obtained through the application of western democratic system.